Can COMT‐inhibitor delay the clinical progression of Parkinson's disease? 2 years follow up pilot study. Issue 1 (March 2016) - Song, In‐Uk; Kim, Tae‐Won; Yoo, Ikdong; Chung, Yong‐An; Lee, Kwan‐Sung
ABSTRACT: Hyperhomocysteinemia is associated with the severity of human neurodegenerative diseases due to its neuronal and endothelial toxicities, and pretreatment of a catecho‐O‐methyltransferase (COMTI) could block thel ‐dopa induced elevation of serum Hcy levels in preclinical study. However, it is unclear whether hyperhomocysteinemia in the patients with Parkinson's disease (PD) is related to clinical progression or not. Therefore, we conducted this 2‐year follow‐up study to evaluate whether or not COMTI has an impact on the progression or severity of PD. Data for 50 PD patients (22 PD patients treated withl ‐Dopa and COMTI and 28 PD patients treated withl ‐Dopa alone) who were recruited for this study were compared with those of 19 healthy controls. All subjects underwent Tc‐99m HMPAO SPECT and neurological evaluation including cognitive function. Serum homocysteine (Hcy) was measured at baseline and at the 2‐year follow up visit. The result showed serum Hcy levels were greater in the two PD groups than the healthy control group ( P  = 0.003), suggesting L‐dopa induced hyperhomocysteinemia. However, the comparison between these two PD groups showed no significant differences in serum Hcy level as well as regional cerebral perfusion, cognitive function or motor severity at baseline and at 2 years, indicating that COMTI neither preventedl ‐dopa induced hyperhomocysteinemia nor delayed clinical progression. Given limitation of excluding advanced PD with late motor complications, future large‐scale long‐term followup studies are needed to clarify the effects of COMTI.